Upper Mantle P and S Wave Velocity Structure of the Kalahari Craton and Surrounding Proterozoic Terranes, Southern Africa - Kameron Ortiz; Andrew Nyblade; Mark van derMeijde; Hanneke Paulssen; Motsamai Kwadiba; Onkgopotse Ntibinyane; Raymond Durrheim; Islam Fadel; Kyle Homman (Geophysical Research Letters)
Abstract New broadband seismic data from Botswana and South Africa have been combined with existing data from the region to develop improved P and S wave velocity models for investigating the upper mantle structure of southern Africa. Higher craton‐like velocities are imaged beneath the Rehoboth Province and parts of the northern Okwa Terrane and the Magondi Belt, indicating that the northern edge of the greater Kalahari Craton lithosphere lies along the northern boundary of these terranes. Lower off‐craton velocities are imaged beneath the Damara‐Ghanzi‐Chobe Belt, and may in part reflect thinning of the lithosphere beneath the incipient Okavango Rift. Lower velocities are also imaged to the north and northwest of the Bushveld Complex beneath parts of the Okwa Terrane, Magondi Belt, and Limpopo Belt, indicating that cratonic upper mantle in some areas beneath these terranes may have been modified by the 2.05‐Ga Bushveld and/or 1.1‐Ga Umkondo magmatic events.